Feedback control of dynamic systems - Franklin, Gene F; Powell, J. David, 1938-; Emami-Naeini, Abbas (Upper Saddle River [N.J.] : Pearson, 2010)
"This revision of a top-selling textbook on feedback control provides greater instructor flexibility and student readability. Chapter 4 on A First Analysis of Feedback has been substantially rewritten to present the material in a more logical and effective manner. A new case study on biological control introduces an important new area to the students, and each chapter now includes a historical perspective to illustrate the origins of the field. As in earlier editions, the book has been updated so that solutions are based on the latest versions of MATLAB and SIMULINK."--BOOK JACKET
1. Overview and Brief History of Feedback Control -- 2. Dynamic Models -- 3. Dynamic Response -- 4. First Analysis of Feedback -- 5. Root-Locus Design Method -- 6. Frequency-Response Design Method -- 7. State-Space Design -- 8. Digital Control -- 9. Nonlinear Systems -- 10. Control System Design: Principles and Case Studies -- Appendix A : Laplace Transforms -- Appendix B : Solutions to the Review Questions -- Appendix C : MATLAB Commands
Includes bibliographical references (p. 793-799) and index
Keywords: Feedback control systems